NEGOTIATING PROFESSIONAL BELONGINGS: FINNISH ACTORS’ AFFECTIVE ENGAGEMENTS ON SOCIAL MEDIA PLATFORMS - Soronen, Anne; Koivunen, Anu (AoIR Selected Papers of Internet Research, 2021)
This study addresses how creative workers’ social media presence affects their understandings of professional agency. Focusing on Finnish professional actors, we ask how social media practices inform and shape actors’ occupational self-conceptions and professional belongings. In the theoretical framework, we employ Baym’s notion of relational labour and read it through Berlant’s (1998) conceptualisation of intimacy as mobile attachments. The data is collected from 15 Finnish actors, eight freelancers and seven theatre employees, from June 2020 to March 2021 by using the diary-interview method. The analysis is based on a close reading of the interview material and diary entries in which participants describe their experiences and feelings concerning their presence, work-related connections, and promotion on Facebook and Instagram. The study indicates that for both theatre actors and freelancers their social media activities are entwined in their sense of professionalism and belongings to occupational communities of peers. They negotiate and speculate about their social media presence in relation to peer assessments in a way that involves continuous movements between visibility and invisibility and between independence and interdependence. Our study suggests that to understand the ambivalences involved in creative workers’ presence on social media platforms, it is important to broaden the investigation from strategic self-promotion and audience engagement to questions of professional identities and communities.